2015
DOI: 10.1590/s0100-736x2015001000007
|View full text |Cite
|
Sign up to set email alerts
|

Fecal cortisol metabolites as indicators of stress in crab-eating-fox (Cerdocyoun thous) in captivity

Abstract: Blood samples collection is a common method in biological research using domestic animals. However, most blood sampling techniques are complicated and highly invasive and may therefore not be appropriate for wildlife animals in research concerning stress. Thus, a non-invasive method to measure steroid hormones is critically needed. The first goal of this study was to determine how glucocorticoids concentrations are impacted by translocation and reproductive activity in crab-eating-fox (Cerdocyoun thous) in cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…These wolves' fGC glucocorticoid concentrations returned to basal levels 2 days after the husbandry procedures. Likewise, the translocation of a male to a female enclosure resulted in a 3.5-fold increase compared to baseline concentrations in foxes (Cerdocyoun thous Linnaeus, 1766) (Paz et al 2015), and two-fold elevated fGC concentrations were observed 1 day after a veterinary procedure in zoo-housed armadillos (Tolypeutes matacus Desmarest, 1804) (Howell-Stephens et al 2012). Our results also agree with Creel et al (2002), Van Meter et al (2009) andEggermann et al (2013), who state that anthropogenic disturbance may also influence stress hormones.…”
Section: General Datasupporting
confidence: 88%
See 1 more Smart Citation
“…These wolves' fGC glucocorticoid concentrations returned to basal levels 2 days after the husbandry procedures. Likewise, the translocation of a male to a female enclosure resulted in a 3.5-fold increase compared to baseline concentrations in foxes (Cerdocyoun thous Linnaeus, 1766) (Paz et al 2015), and two-fold elevated fGC concentrations were observed 1 day after a veterinary procedure in zoo-housed armadillos (Tolypeutes matacus Desmarest, 1804) (Howell-Stephens et al 2012). Our results also agree with Creel et al (2002), Van Meter et al (2009) andEggermann et al (2013), who state that anthropogenic disturbance may also influence stress hormones.…”
Section: General Datasupporting
confidence: 88%
“…Measurement of glucocorticoid metabolites in scats has become a widely employed and accepted method for the non-invasive evaluation of adrenocortical response to stressors in carnivores (Goymann et al 1999;von der Ohe & Servheen 2002;Sands & Creel 2004;Young et al 2004;Paz et al 2015). As part of a more comprehensive study on physiological stress and reproductive behaviour in captive Mexican grey wolves, we sought to analyse the effects of breeding season, social rank, pack social grouping, gender and age on the quantification of faecal concentrations of glucocorticoid metabolites within six wolf facilities in a longitudinal study.…”
Section: Introductionmentioning
confidence: 99%
“…As part of a FCM validation study in crab-eating foxes, Paz et al ( 2014) found a 10-45 fold increase in FCMs after ACTH injections compared to baseline values. Later, the authors recorded FCM to examine welfare related effects of rehousing and reproduction in these foxes (Paz et al, 2015). Our data are the first to look for similar effects in silver foxes, and will now be used in fox welfare research.…”
Section: Discussionmentioning
confidence: 77%
“…1 and the A non-invasive alternative is the use of faecal samples. Studies in which faecal glucocorticoids were assessed were conducted in elks Cervus elaphus (Millspaugh et al 2001), mourning doves Zenaida macroura (Washburn et al 2003), greater sage grouse Centrocercus urophasianus (Jankowski et al 2009), African bush elephants Loxodonta africana (Munshi-South et al 2008, Ahlering et al 2013, Columbian ground squirrels Urocitellus columbianus (Bosson et al 2009), common degus Octodon degus (Soto-Gamboa et al 2009), giant pandas Ailuropoda melanoleuca (Yu et al 2011), aardwolves Proteles cristata (Ganswindt et al 2012), eastern chipmunks Tamias striatus (Montiglio et al 2012), coyotes Canis latrans (Schell et al 2013), crab-eating foxes Cerdocyoun thous (Paz et al 2015), marmots Marmota flaviventris (Wey et al 2015), woylies Bettongia penicillata (Hing et al 2017), pikas Ochotona princeps (Wilkening et al 2016), North Atlantic right whales Eubalaena glacialis (Hunt et al 2006) or primates (Behringer and Deschner 2017). In frogs, dermal swabs (Santymire et al 2018) or urine samples (Narayan et al 2010, Narayan 2013 collected by gentle massage of the lower abdomen can be used for the analysis.…”
Section: Physiologymentioning
confidence: 99%